Design and Construction of Smart Garage Using Ultrasonic Sensor HC-SR04 and MQ-2 Gas Sensor Based on Arduino Uno - Mariza Wijayanti (SEAN Institute, 2022)
The trash can is a place for humans to throw garbage, but the problem that arises is the laziness of humans to dispose of garbage in its place due to the dirty cover of the trash can, besides that smelly trash cans can also disturb people around them. Therefore, a tool is designed that can work to make it easier for humans to dispose of garbage in its place, dispose of garbage that already smells bad, and help cleaners in emptying the trash in a timely manner. Smart trash cans are the answer to the problem of people's laziness in disposing of garbage, foul-smelling garbage and the delay of cleaning staff in emptying the trash. Working with Arduino UNO, this tool is expected to be able to open the trash can cover automatically and notify if the existing garbage smells bad. By using an ultrasonic sensor and providing an indicator to the cleaning staff through the sound produced by the buzzer, this tool works when the foot or garbage is within the range of the ping sensor. In addition, the Buzzer function on this tool is to notify that the existing garbage has disturbed the human sense of smell. This can help humans in disposing of their trash without touching the lid of the trash can, emptying the trash in a timely manner, and reducing humans to inhale bad odors from existing trash cans